Expert consensus from the Arabian Gulf on selecting disease-modifying treatment for people with multiple sclerosis according to disease activity. Issue 4 (18th May 2020) - Alroughani, Raed; Inshasi, Jihad; Al-Asmi, Abdullah; Alqallaf, Abdulradha; Al Salti, Abdulla; Shatila, Ahmed; Boshra, Amir; Canibano, Beatriz; Deleu, Dirk; Al Sharoqi, Isa; Al Khabouri, Jaber
ABSTRACT: Recent research has expanded our understanding of the natural history and clinical course of multiple sclerosis (MS) in the Arabian Gulf region. In addition, the number of available therapies for MS has increased greatly in recent years, which complicates considerably the design of therapeutic regimens. We, an expert group of physicians practising in Arabian Gulf countries, present pragmatic consensus recommendations for the use of disease-modifying therapy, according to the level of MS disease activity, according to objective criteria, and prior treatment (if any) received by a given patient.